DEVELOPMENT VALIDATION OF QUERCETIN COMPOUNDS USING RP-HPLC AND IN VITRO ACTIVITY STUDIES ON MELASTOMA MALABATHRICUM LEAF NANOCREAM FOUNDATION PREPARATIONS: - - APRIDAMAYANTI, PRATIWI; SARI, RAFIKA; PRATIWI, LIZA (International Journal of Applied Pharmaceutics, 2023)
Objective: A simple, accurate, precise, sensitive, and robust analytical method has been developed to analyze quercetin in the nano-cream foundation formula added to the ethyl acetate fraction of Melastoma malabathricum leaves. Methods: The validation is consistent with ICH guidelines using a reversed-phase HPLC method with mobile-phase acetonitrile-phosphoric buffer conditions at pH 5.51 (40:60 v/v). The stationary phase has a C-18 column, a 0.5 ml/min flow rate, and an Ultraviolet detector at wavelength 370 nm. Furthermore, antioxidant activity testing used the FRAP method, and the SPF value was measured using a Elisa reader with wavelength 615nm and UV/Vis spectrophotometer in the wavelength range of 290-390 nm. Results: The results showed that the retention time of quercetin was 11.462 min with a tailing factor of 1.045. Regression equation y=170220x-85497 had a concentration range of 3-18 µg/ml and a correlation value of 0.9998. The limit of Detection (LOD) and Limit of Quantification (LOQ) were 0.236 and 0.786 µg/ml, respectively. The accuracy method for the recovery value at concentration levels of 80%, 100%, and 120% was 95.233%-109.446%. The repeatability of intra-day and inter-day variations express the %RSD values of 1.258-1.378% and 1.012-1.258%. Meanwhile, the method's strength by changing the column temperature, maximum wavelength, mobile phase composition, and the flow rate was expressed by the %RSD value of 0.045-0.067%, 0.069-1.642%, 0.107-0.165%, and 0.141-0.318%, respectively. The analysis results of the quercetin content in the nano cream foundation formula were 0.021728±5.83x10-4 mg/g. Antioxidant activity with an IC50 value was 1444.157±15.538 µg/ml, and the SPF at a concentration of 8000 µg/ml was 11.370±1.083. Conclusion: The development method of quercetin is simple, accurate, precise, sensitive, and robust. Quantitative analysis of quercetin biomarkers in nano cream preparations containing the ethyl acetate fraction of Melastoma malabathricum leaves using the RP-HPLC method.